FILSAFAT DAN KONSEP KEMITRASEJAJARAN DI INDONESIA - Septiana Dwiputri Maharani (Populasi, 2004)
Female autonomy as humans, enforced by social norms and society is a result of a world that still follows traditionalpatriarchal paradigms. Males are still always luckier than women in a range of areas and this means that women do not receive the opportunity to use their autonomy to its optimal level. Violence and the violation of womens' rights are factors in the identification of injustices towards women. It is extremely difficult in the current environment for women to carry out activities based on their potential as part of the world. Philosophy gives us insight that should be used to solve the aforementioned problem. However in reality, philosophy itself is formed by patriarchal paradigms. ^s one of the roots of Indonesian philosophy, Javanese philosophy states suwarga nunut neraka katut dan kanca wingking (heaven goes by hell follows and friends are left behind) meaning that women are second class members of society and are weak. In conclusion, the weakness of philosophy is that it is not able to break through the patriarchal paradigm to build perceptions that are not gender bias.